Réponses

2014-02-01T23:47:46+01:00
Bonsoir,

cos(5π/12) = cos(6π/12 - π/12)
                = cos(π/2 - π/12)
                = cos(π/2)cos(π/12) + sin(π/2)sin(π/12)
                = 0*cos(π/12) + 1*sin(π/12)
               = sin(π/12)

or sin²(π/12) + cos²(π/12) = 1 ===> sin²(π/12) = 1 - cos²(π/12)
                                           ===>  sin²(π/12)  = 1 - a²
                                           ===> sin(π/12) = √(1 - a²)

Donc cos(5π/12) = √(1 - a²)

*********************************************
cos(7π/12) = cos(6π/12 + π/12)
                = cos(π/2 + π/12)
                = cos(π/2)cos(π/12) - sin(π/2)sin(π/12)
                = 0*cos(π/12) - 1*sin(π/12)
               = -sin(π/12)

or  sin(π/12) = √(1 - a²)

Donc cos(7π/12) = -√(1 - a²)

*********************************************

cos(π/6) = ?

On utilise la formule suivante : cos(2x) = 2cos²x - 1  avec x = π/12

cos(π/6) = cos(2 * π/12)
             = 2cos²(π/12) - 1
             = 2a² - 1